Establishment and maintenance of a colony of the Old World Screwworm fly Chrysomya bezziana at Balitvet in Bogor, West Java, Indonesia - ., Sukarsih; Partoutomo, Sujitno; Tozer, Robert; Satria, Edy; Wijeffels, Gene; Riding, George (Indonesian Animal Sciences Society, 2000)
A colony of the Old World Screwworm fly, Chrysomya bezziana, has been established and maintained at Balai Penelitian Veteriner, Bogor, West Java, Indonesia since 1994. Culture on a convenient, defined diet able to sustain long term reproducibility of insect performance is described. The long-term viability of the colony has been further assured with an effective and reliable culturing procedure, with the genetic diversity and robustness of the colony being maintained through regular infusions of wild-type field isolates. The colony has been a reliable source of larval material used for the isolation and identification of protective antigens in the ACIAR funded Screwworm Fly Vaccination Project. Larvae have been used in the development and routine application of assays employed to evaluate vaccine efficacy. The colony continues to be a valuable resource for both screwworm fly vaccine and other new research includi the evaluation of screwworm fly attractants and lures. Â Key words: Chrysomya bezziana, culture, colony, larvae, vaccination